Pengaruh Kecerdasan Emosional dan Motivasi Belajar Siswa terhadap Prestasi Belajar IPS - Erlis Thertina (Universitas Indraprasta PGRI Jakarta, 2023)
In understanding and absorbing social studies lessons, each child is different. This difference is whatmakes the achievements of each child also different. Factors that determine student achievement arelearning motivation and emotional intelligence. Students who have motivation to learn will have theself-awareness to manage their emotions so they are able to study seriously. The aim of this research isto find out whether there is an influence of emotional intelligence and learning motivation on students'social studies learning achievement, especially at private junior high schools in East Jakarta. Theresearch was conducted quantitatively using a survey method with multiple regression analysistechniques. Collecting data by distributing questionnaires and multiple choice item tests. The populationcame from class VIII students at private junior high schools in East Jakarta with a sample of 90 studentsfor the 2022/2023 academic year. The results of the research concluded that there was an influence ofemotional intelligence and student learning motivation together on students' social studies learningachievement with a contribution of 40.6% as well as an influence of emotional intelligence on learningachievement of 12.67%, and the influence of students' learning motivation on social studies learningachievement amounting to 13.5%.